Moringa oleifera extract and neostigmine confer neuroprotection on aluminium chloride -induced Alzheimer’s disease: Antioxidant and acetylcholinesterase inhibitory activities - Finbarrs-Bello, Elizabeth; Jude, Okamkpa Chikezie; Ekene, Okoro Gabriel (Journal of Medicinal Herbs and Ethnomedicine, 2022)
Alzheimer’s disease (AD) is a neurological episode associated with the senescence process characterized by neuronal cell death in brain regions and loss of cognition. The study investigate the neuroprotective potentials of Moringa oleifera leaf extract and Neostigmine in a rat model of Alzheimer’s disease induced by Aluminium chloride (AlCl3). A total number of 20 rats weighing 180-240 kg were used for this study and they were grouped into 5 with 4 rats in each group (n=4) labelled A-E. Group A control, received 0.1 mL normal saline (placebo), Group B, received 100 mg/kg of Aluminium chloride, Group C was given Aluminium chloride 100 mg/kg and 200 mg/kg, Group D experimental animals received Aluminium chloride 100 mg/kg and were treated with 400 mg/kg of the extract orally for 21 days, while Group E received the same dose of Alcl3 and 2 mg/kg Neostigmine given intraperitoneal (IP). Thereafter, the rats were sacrificed, and the hippocampi were harvested for histology and histochemical analysis. Our findings revealed visible protective changes in the group treated with the M. oleifera and Neostigmine as the pyramidal cells of CA3 and neurofibrillary tangles which were prominent in the positive control group were resolved. At the end of this study, it was proven that the toxicity induced by Aluminium chloride was reduced by M. oleifera leaf extract and Neostigmine. M. oleifera is a commonly consumed plant therefore the intake should be encouraged.